Quasi-exact treatment of non-relativistic generalized hyperbolic potentials. (1st February 2023) - Rath, Biswanath; Sedaghatnia, Parisa; Hassanabadi, Hassan
Abstract: The solution of the Schrödinger equation for the two quasi-exactly solvable potentials is presented using the Lie algebra approach. It is shown that all models give rise to the same basic differential equation which is quasi-exactly solvable. The eigenvalues, eigenfunctions and the allowed potential parameters are given for each of the two models in terms of the roots of a set of algebraic quasi-exact solvable methods.